Potential of Compost and Bio Fertilizer Combination in Improving Growth and Yield of Red Curly Chili - Indra Permana; Leny Yuliyani; Panji Rahmatullah; Indra Ardiansyah; Tirta Kumala Dewi; Entis Sutisna (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Red curly chili production in Indonesia is currently falling short of expectations. The objective of this research was to evaluate the affectivity of bio fertilizer and compost combination in increasing growth and yield two varieties of red curly chili in Rancamaya, Bogor. Split plot design was used as an experimental design with different variety of red curly chili (OR Twist = V1 and Kencana = V2) as main plot and fertilizer (A = Control without chemical fertilizers + Compost + POH, B = 50% Chemical Fertilizer + Compost + POH, C = 75% Chemical Fertilizer + Compost + POH, D = 100% Chemical Fertilizer + Compost + POH, E = 100% Chemical Fertilizer + manure, F = 100% Chemical Fertilizer) combination as sub plot. The collected data was analysed by using ANOVA with 5% of significancy, a further test is performed using duncan mutiple range test. OR Twist variety showed the highest growth performance on plant height with 26.4 cm (21 DAP), 56.3 cm (35 DAP), and 82.8 cm (DAP) and leave number by 86.8 and 285 leaves at 35 and 39 DAP. The highest cumulative yield of red curly chili was resulted by OR Twist variety from 1st until 5th harvesting period. OR Twist variety and 50% chemical fertilizer treatment with the addition of compost and POH was the best combination in increasing average fruit weight and cumulative of red curly chili at Rancamaya, Bogor.